A new and simple technique for vagal ganglia ablation in a patient with functional atrioventricular block: Electroanatomical approach - Tolga Aksu; Tumer Erdem Guler; Kivanc Yalin; Serdar Bozyel; Ferit Onur Mutluer (KARE Publishing, 2018)
Increased parasympathetic tone may cause symptomatic functional atrioventricular block (AVB) and necessitate pacemaker implantation. In these patients, where there is no structural damage to the conduction system, removal of the vagal activity using radiofrequency ablation seems to be a theoretically rational approach. Several methods have been used to determine suitable areas for vagal ganglia ablation. The aim of this report was to describe a new method to detect parasympathetic innervation sites without the need to use additional equipment or extend procedure time. A 51-year-old man was referred to the clinic for implantation of a permanent pacemaker because of symptomatic second-degree AVB and recurrent syncope. The functional nature of the AVB and a supra-Hisian location were verified with standard electrocardiography, Holter recordings, atropine sulfate test, and a standard electrophysiological study. Using conventional recordings, the electrograms were divided into 3 subgroups and sites demonstrating a fractionated pattern were targeted. All of the fractionated electrogram sites considered suitable for usual ganglion settlement were ablated. Biatrial ablation was initiated from the left atrial side. During left atrial ablation, the intrinsic basic cycle length of sinus node accelerated to 800 milliseconds despite AVB persistence. Subsequently, 1: 1 atrioventricular conduction was achieved when ablation was applied around the coronary sinus ostium. The patient was completely asymptomatic, experiencing no episodes of dizziness or syncope, and was taking no medications at the end of 9 months of follow-up. In conclusion, electroanatomically guided vagal ganglia ablation may be a good alternative to pacemaker implantation in well-selected patients with functional AVB.